HUBUNGAN ANTARA DUKUNGAN TEMAN SEBAYA DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA TAHUN KELIMA YANG SEDANG MENGERJAKAN SKRIPSI DI FAKULTAS ILMU BUDAYA DAN FAKULTAS PSIKOLOGI UNIVERSITAS DIPONEGORO - Woro Inten Sayekti; Dian Ratna Sawitri (Faculty of Psychology, Diponegoro University, 2018)
The purpose of this research is to examine the relationship between peer support and academic procrastination in fifth year students who are working on thesis in Faculty of Humanities and Faculty of Psychology Diponegoro University, and know the effective contribution of peer support to academic procrastination. The population of this research is the fifth year student of Faculty of Humanities and Faculty of Psychology Diponegoro University who is preparing thesis. The sample of 104 students was obtained with convenience sampling. Data collection used two scales, Academic Procrastination Scale (31 items; α = 0,91) and Peer Support Scale (37 items; α = 0,94). Simple regression analysis showed a significant negative correlation between peer social support and academic procrastination in fifth year students who were working on thesis (rxy = -0,31; p = 0,001), and effective contribution of peer support to academic procrastination is 10%.